The contested terrain of alcohol sponsorship of sport in New Zealand. (June 2016) - Cody, Kieran; Jackson, Steve
This study examines the politics and policy implications of alcohol sponsorship of sport in New Zealand. Specifically, it draws on the recommendations of the 2010 New Zealand Law Commission report titled Alcohol in our lives: Curbing the harm, which called for the gradual elimination of all alcohol sponsorship from New Zealand sport. Using a multi-method approach, the paper examines the contested terrain of the alcohol–sport relationship, that is, the nature of the relationship and its potential impact on the nation's binge drinking culture, how it is regulated by both states and sport organisations within the international community and, finally, the perspectives of key stakeholders in the debate. The views of key stakeholders offer insights into the nature of competing interests at play within the alcohol–sport sponsorship relationship. Overall, the findings highlight the challenges of social change and the need for more research and a community-based, multidimensional approach that is reinforced through regulation.